Analysis of Tool Geometry and Hole Quality Effects on Drilling Carbon-Fibre Reinforced Polymer Composites Using ANSYS - Johnson, David; Smith , Clara (Ayden Journal of Engineering and Applied Sciences, 2024)
This study focused on the analysis of the effect of tool geometry and hole quality on drilling carbon-fibre reinforced polymer (CFRP) composite using ANSYS. The experiment was conducted on computer numerical control machine (CNC) using high speed steel (HSS) twist drill bit and HSS-COBALT drill type. Taguchi L9 orthogonal array was used for the optimization analysis. Analysis of variance (ANOVA) was employed to determine the most significant control factors affecting the drilling process. The machining parameters involving tool type, point angle, spindle speed and feed rate were selected as control factors. While the dependable variables on workpiece were cutting force, stress and strain. The main interaction effect of the input variables on the predicted responses was investigated. The ANOVA/F-test results for cutting force with the contribution of each machining parameters revealed that the cutting speed was the dominant factor influencing cutting force developed with a contribution of 57 percent, The second factor affecting cutting force developed was point angle with a contribution of 5.7 percent, while feed rate had the least effect on cutting force developed where its contribution of 1.4 percent. Based on the results observed, the optimal machining parameters that produced minimum stress was observed with HSSCOBALT drill at 118 degrees of point angle, 300 mm/min of feed and 500 rpm of speed. Also from Taguchi results, the optimal combination of process parameters to obtain maximum strain with HSS drill, 135 degrees of point angle, and 300 mm/min of feed and 1500 rpm of speed produced the optimal drilling condition for CFRC polymer within the scope of this research work.